Optimum Phase Number for Multiphase PWM Inverters - Anwar Muqorobin; Pekik Argo Dahono; Agus Purwadi (IAES Indonesia Section, 2017)
This paper investigates the optimum phase number for multiphase PWM inverters. The input current ripple is used as a performance indicator. Analysis results show that phase number more than nine cannot provide significant input current ripple reduction. Experimental results are included in this paper to show the validity of the proposed analysis method.